The importance of managing the psychosocial potential of human resources for employee job satisfaction / Importanța gestiunii potențialului psihosocial al resurselor umane pentru satisfacția cu munca a angajaților - CEBOTARI Veaces (EcoSoEn: Ştiinţe Economice, Sociale şi Inginereşti = Economics, Social and Engineering Sciences)
Job satisfaction is a combination of positive or negative feelings that employees have about their work. Meanwhile, when an employee in an organization brings with him the needs, wants, and experiences that determine the expectations he has built, job satisfaction will represent the extent to which the organization meets them. Job satisfaction is the extent to which expectations match reality. Job satisfaction is closely related to the individual's behavior at work. Job satisfaction is the employee's sense of accomplishment and success. It is generally perceived to be directly related to both productivity and personal well-being. Job satisfaction involves having a job you enjoy, doing well, and being rewarded for your personal efforts. Job satisfaction further implies enthusiasm and happiness at work. Job satisfaction is the essential element that leads to recognition, income, promotion and the achievement of other goals that lead to a sense of self-fulfillment [4]. Job satisfaction can also be defined as the extent to which an employee is satisfied with the rewards he derives from his work, especially in terms of intrinsic motivation.The term job satisfaction refers to the manifestations and feelings that people have towards their work. Positive and favorable attitudes towards the workplace indicate job satisfaction. Negative and unfavorable attitudes towards the workplace indicate job dissatisfaction. Job satisfaction is the collection of feelings and beliefs that people have about their current job. People's job satisfaction levels can range from extreme satisfaction to extreme dissatisfaction. In addition to having attitudes about their jobs as a whole, people may also have attitudes about various aspects of their work, such as the type of work they do, their peers, supervisors or subordinates, and pay them.